(untitled) (Research, Society and Development, 2022)
Neurological rehabilitation is essential for maintaining and increasing the motor function of patients affected by neuropathologies. Some impairments are commonly related to loss of muscle strength, balance and walking ability. Recently, the use of mechanical vibrations associated with conventional treatment to enhance gains in motor rehabilitation has emerged. It is suggested that vibrations increase the motoneurons excitability, contributing to the gait performance, balance and proprioception, in addition to decreasing spasticity. This study aims to implement a retrofit of a parallel bar device with vibratory stimulus and to validate the new system. This improvement targeted at increasing robustness, better mass distribution and an HMI development. To validate the system, engineering tests were performed that included the frequency measurement, vibration intensity, oscillation amplitude and sound emission, besides the system usability measurement by health professionals with the SUS scale. The engineering tests revealed that the improved device allows several protocols execution, since the control variables remain stable regardless of the load application point and that the sound noise is in accordance with Brazilian safety regulations. The device was evaluated by health professionals as “Best Imaginable” on the SUS scale. Through the retrofit performed, the device became more efficient and safer, optimizing this tool for clinical practice.